Ecological Pesantren as an Innovation in Islamic Religious Education Curriculum: Is It Feasible? - Albar, Mawi Khusni; Hamami, Tasman; Sukiman, Sukiman; Roja Badrus Z, Akhmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article examines the innovation of an ecology-based Islamic religious education curriculum as a response to global environmental challenges. The background includes the role of humans as khalīfah, responsible for preserving nature, and the need for education that integrates religious values with ecological principles to foster sustainable behavior. This research also highlights the role of pesantren, traditional Islamic educational institutions, in implementing the ecological curriculum, given their long history of teaching moral and ethical values. The research methodology employs a quasiqualitative approach with literature analysis and case studies of several pesantren that have implemented the ecological curriculum. The findings indicate that integrating Islamic values with ecological principles can enhance environmental awareness, sustainability ethics, and social responsibility within Muslim communities. Pesantren play a crucial role in instilling these values through activities such as organic farming, waste management, and reforestation programs. This curriculum innovation involves a holistic approach that considers the complex interactions between humans, nature, and God. The implications of this research underscore the need for support from various stakeholders, including educational institutions, communities, and governments, in the implementation and development of the ecology-based Islamic religious education curriculum. This curriculum development is expected to serve as a model for Islamic educational institutions worldwide in integrating ecological values into religious education.